“汉服热” 的起源与商业化进程研究 = A study of Hanfu (ethnicity apparels of Hans) : re-popularization and commercialization - 关慧华 Guan, Huihua (Nanyang Technological University, 2020)
汉服是汉族传统服饰的统称。汉服复兴在 1913-1930 年间曾发生过一次，不过那时只是昙花 一现。随着二十一世纪大数据时代的来临，大量出土文物的数据资料被公开，许多文献资料便可 以轻而易举地得到。同时，网络论坛的兴起也让更多人开始讨论关于汉民族传统服饰的代表性。 “汉服”作为一个文化的符号，它所代表的服饰文化也进入社会民众的视野里，逐渐引发人们对 于“汉服”的服饰以及历史文化研究。 近年来，随着文化复兴浪潮的兴起，“汉服”频繁地出现在大众视野里。随着热爱汉服的群 体不断壮大，“汉服”也为服饰商家提供了新的行销方案和商业思路，更多不同类型的时尚服装 元素被加以融合在汉服设计，进行新的创新和改良。在这些新款汉服推出之后，又引出了两种不 同派别对此的争论。 本文将追溯“汉服热”兴起的源头来发掘汉服所蕴含的文化意义，进而阐释互联网对“汉服 文化”的推动性，紧接着商讨“汉服”在经历商业化后所带来的时尚元素融合和进行改良趋势， 为现存“汉服”版型的争论议题进行探讨和归纳。 Hanfu is the transliteration name of traditional ethnicity apparels of Hans. Hanfu Renaissance has occurred between 1913 to 1930, but it only lasted for a short period of time. As the 21st Century Big Data Era arrives, many ancient cultural relics data were retrieved and the data base was open for public knowledge. At the same time, rising of Internet Forum allows people to discuss about the representative traditional apparels of Hans, which now discovered and known as Hanfu. Hanfu, as an iconic symbol and representative of Hans culture, the beauty of it comes to the mind of the people, resulting in people starting discussion about the cultural and history value behind it. In recent years, as the rise of the wave of cultural renaissance, Hanfu has been repeated being widely used and discussed. As more and more people talk about it, it provides the apparel merchandisers new marketing plans and business mindsets. To provide and boost sales, elements and ideas from different aspects close to the recent fashion are used when designing Hanfu, to create Hanfu in a more innovation and improvisation way. As a result, debates from two different sides of the audience starts. In this article, I would trace back the start of re-popularization of Hanfu’s to discover the cultural values behind it, so as to interpret how internet has actually place a huge part in promoting Hanfu Culture. Also, I would discuss the commercialization of Hanfu and what it brings about of changing the design of it. Lastly, summarize up the edition type of Hanfu and the faction debate behind it.